Microsatellite instability in melanoma: a comprehensive review - Kubeček, Ondřej; Kopecký, Jindřich (Melanoma research, 2016)
Microsatellite instability (MSI) and mismatch repair deficiency are an emerging issue in oncology and molecular pathology. Besides being associated with better clinical outcome in colon cancer, MSI also harbors the potential to predict response to chemotherapy and immunotherapy. MSI was also observed in other solid tumors, including endometrial cancer, ovarian cancer, and melanoma, besides colon cancer. Strong evidence shows that MSI is a frequent event in melanoma. However, the data on MSI prevalence, pathogenesis, and clinical consequences in melanoma are limited. Therefore, we summarize the current knowledge on MSI in melanoma and outline future perspectives and clinical implications, including its role as a prognostic and/or a predictive factor.
Keywords: oprava chybného párování bází DNA; nádory kůže; Immunotherapy; lidé; melanom; imunoterapie; mikrosatelitní nestabilita; Skin Neoplasms; DNA Mismatch Repair; Microsatellite Instability; Melanoma; Humans